RELATIONSHIPS BETWEEN INFORMATION SECURITY, CYBER SECURITY IN THE CONTEXT OF UKRAINE’S SECURITY STRATEGIES 2020-2021 - Belkin, Leonid; Іurynets, Juliya; Belkin, Mark; Kryvolap, Ievgenii (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The aim of the article is a comprehensive legal and information technology analysis of the concepts of «information security», «cybersecurity» to justify the approach to creating a central definition in the field of information security and improving the system of combating information threats. Research methods: documentary analysis, generalization of legal information, information in the field of information and communication technologies, as well as practices of information protection and counteraction to propaganda information and psychological influences. Results: taking into account the provisions of the security strategies of Ukraine 2020-2021, as well as scientific, practical information and international experience, the structure of «information security of the state» as a central definition in the field of information security is proposed. It is argued that the concept of «information security» cannot be reduced to the security of a single set of data or information systems or to cybersecurity. Information security is divided into cybersecurity and cognitive security. It is proposed to introduce into stable scientific and practical circulation the concept of «cognitive security» as resistance to information and psychological influences on man and society. The feedback «cybersecurity» → «cognitive security» is due to the fact that cyber attacks are also actively used by the aggressor state as an element of special information operations to manipulate the population. Discussion: a comprehensive legal and information technology analysis of the concepts of «information security», «cybersecurity» allows you to build a hierarchy of these concepts in order to improve countering information threats and propaganda information operations.